Implicit stereotyping role in the person’s traits forecasting - Martišius , Vaclovas (Psichologija, 2000)
In the main part of this work subjects were exposed to four target’s traits. Each participant evaluated a likehood of some other traits on seven-point scale. There could be made conclusion from the exploration data that ratings of female and male targets were statistically equivalent. Also there was not confirmed an opinion that higher stereotyping level causes more intensive implicit stereotyping. Individuating information strongly influenced judgments of targets.